2002
DOI: 10.1021/jf025550q
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Mediated Solvent Extraction of Carotenoids from Marigold Flower (Tagetes erecta)

Abstract: Marigold flowers are the most important source of carotenoids for application in the food industry. However, the extraction gives almost 50% losses of the carotenoids depending on conditions for silaging, drying, and solvent extraction. In the past decades, macerating enzymes have been successfully applied to improve the extraction yield of valued compounds from natural products. In this work, an alternative extraction process for carotenoids is proposed, consisting of a simultaneous enzymatic treatment and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(70 citation statements)
references
References 13 publications
(19 reference statements)
5
60
1
Order By: Relevance
“…This increment can be explained in terms of the hydrolytic capacity of enzymes to degrade the main components of the cell wall, releasing sugars from macro-molecules like cellulose, hemicellulose and pectin. A similar behavior has been referenced previously by Barzana et al (2002) for the carotenoids extraction from marigold flower flowers.…”
Section: Enzymatically-aided Antioxidant Extraction Processsupporting
confidence: 80%
“…This increment can be explained in terms of the hydrolytic capacity of enzymes to degrade the main components of the cell wall, releasing sugars from macro-molecules like cellulose, hemicellulose and pectin. A similar behavior has been referenced previously by Barzana et al (2002) for the carotenoids extraction from marigold flower flowers.…”
Section: Enzymatically-aided Antioxidant Extraction Processsupporting
confidence: 80%
“…Of these solvents, lutein is most soluble to dichloromethane and acetone and, to a lesser extent, to hexanes and alcohols (Craft and Soares 1992) where free lutein is concerned. Barzana et al (2002) showed that free lutein is less prone to isomerisation and degradation in hexane, which might be a benefit, although the solubility is lower. It has to be noted, that the solubility of free lutein differs immensely from the solubility of lutein esters in some solvent systems (Amar et al 2003).…”
Section: Lutein Oil Extraction Emulsion Stability Polysaccharidesmentioning
confidence: 99%
“…Such benefits can be obtained using careful grinding but also enzyme-assisted extraction. Barzana et al (2002) tested some combinations of plant cell wall degrading enzymes and hexane extraction, and they reported extraction efficiencies of up to 97 percent.…”
Section: Lutein Oil Extraction Emulsion Stability Polysaccharidesmentioning
confidence: 99%
“…Accordingly, more pigment (anthocyanin) was extracted during the vinification process, when enzymes were applied on grape skin (PiemoliniBarreto et al, 2014). In another example, the extraction of carotenoids from marigold flower or tomato skin (Barzana et al, 2002;Dehghan-Shoar et al, 2011) indicates that enzymes can also be useful for the extraction of bioactive compounds from other plant sources.…”
Section: Parametersmentioning
confidence: 99%